Over-current protection device and manufacturing method thereof - FENG HUI MING; LI WEN CHIN (2012)
An over-current protection device comprises a PTC material layer, a first electrode layer, a second electrode layer, a first side electrode and a second side electrode. The PTC material layer is sandwiched between the first electrode layer and the second electrode layer. The first side electrode and the second side electrode are respectively disposed on two opposite side surfaces of the PTC material layer, and are respectively connected to the first electrode layer and the second electrode layer. Furthermore, the first side electrode and the second side electrode are respectively extended to four surfaces adjacent and perpendicular to the two side surfaces.